2015
DOI: 10.1039/c5ra06620d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the thermotropic properties of liquid crystalline p-substituted aroylhydrazones

Abstract: Lamellar smectic A to columnar mesophase crossover is observed in p-substituted aroylhydrazones by variation of the alkoxy chain density at peripherals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…The obtained data were tested for Langmuir adsorption isotherm, which can be represented by the eqn (11),…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained data were tested for Langmuir adsorption isotherm, which can be represented by the eqn (11),…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…In this scenario, Schiff bases are studied extensively due to the presence of >C]Ngroups which allow the corresponding Schiff bases to get adsorbed on the surface of mild steel and to form a monolayer on the surface spontaneously. Therefore, it can act as an effective corrosion inhibitor 8,9 for mild steel, [10][11][12][13] stainless steel, 14,15 iron, nickel, 16 copper, 17 aluminum, 18 and alloy, 19 in various aggressive solutions. The Schiff base ligands form stable complexes closely packed in the coordination sphere of metal ion to generate another class of compounds for corrosion inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At room temperature amide CO stretching vibrations at ~1650 confirms the intermolecular hydrogen bonding between the amide groups . These CO bonds are likely to form intermolecular hydrogen bonds in the LCs containing amide linking group particularly in aryolhydrazones . At Cr I → Cr II transition, the amide band shifts higher to 1656 cm −1 .…”
Section: Resultsmentioning
confidence: 84%
“…In continuation of earlier studies, we have shown that aroylhydrazone forms a suitable core for the design of liquid crystals capable of undergoing lamellar smectic mesophases in mono alkoxy chain derivatives . Recently, we have shown that presence of nonflexible (imine) substituent at aryolhydrozone core leads to complete breaking of intermolecular hydrogen bonding and formation of SmA phase . To the best of our knowledge, studies on origin of frequently observed tilted lamellar SmC mesophase has not been performed so far.…”
Section: Introductionmentioning
confidence: 95%